Propuesta de implementación de un plan operativo para optimizar la gestión económica y financiera de la Notaria Anticona - provincia de Trujillo - Alva Linares, Carlos Eduardo (2017)
The objective of the presentation study was to determine the implementation of an Operational Plan at ‘‘Anticona’’ Notary, located in La Esperanza, with the purpose to develop the importance of proper management of the areas implicated to get better economic and financial results of the enterprise. The present research has a scope of influence at institutional level and also at the provincial level because of the important presence in companies that generate employment and economic stability in the region. At the same time, this research was just with the use of several data collection instruments, applying an interview to the Notary public of the enterprise, who permit us to evaluate certain important points within the ‘‘Anticona’’ Notary. In addition, it was access to the financial statements of 2014 and 2015 which served to analyze the economic and financial situation, applying tables and graphs. In conclusion, we determine that the implementation of an Operational Plan has been highly significant in the different areas of the entity, allowing better administrative and financial management, taking on new policies, procedures and functions, which will make the best decisions.